ONE FACTOR RESPONSE SURFACE METHODOLOGY (RSM) FOR THE OPTIMIZATION OF ORAL VENLAFAXINE HCL CONTROLLED RELEASE ORGANOGEL - OZA, NISHANT; MAKWANA, AMI; GOHIL, TUSHAR A. (International Journal of Applied Pharmaceutics, 2022)
Objective: The aim of this study was to develop the oral Venlafaxine HCl controlled-release organogel (organogel–CR) by using one-factor response surface methodology (RSM). Methods: In this study, Drug-excipient compatibility was evaluated by FT-IR. A total of 14 experimental runs were carried out employing the detailed conditions designed by a single factor completely randomized design based on the response surface methodology was used to check the concentration effect of 12-Hydroxy stearic acid (12-HSA) at different cooling rates on drug release at 10 h (Q10) and after 12 h (Q12). Multiple linear regression analysis, analysis of variance (ANOVA) and graphical representation of the influence factor were performed by using design expert 12. The developed organogel was also evaluated for viscosity, strength, transition temperature, diffusivity and Scanning electron microscopy (SEM). Prepared organogel was filled in the capsule and investigated for weight variation, drug content, erosion of organogel and In vitro drug release study. Results: FT-IR results showed that there was no chemical interaction between the drug and excipients. The SEM photograph indicates that the developed organogel was highly viscous with 3D network structure. The experimental confirmation tests showed a correlation between the predicted and experimental responses (R2 = 0.9937 and 0.9709). The results of ANOVA suggested that calculated F values of all dependent variables are greater than tabulated values. The optimal point obtained was located in the valid region and the optimum in vitro release of the predicted batch containing 7.9% concentration of 12-HSA with gradual cooling rate. To validate the evolved mathematical models, a checkpoint was selected and its desirability value was found to be 0.866. Conclusion: Oral controlled release Venlafaxine HCl organogel fix the problem of repeated dosing and patient noncompliance.